1995
DOI: 10.1177/026835559501000304
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Varicose Veins and Primary Deep Venous Insufficiency: Relationship and Therapeutic Implications

Abstract: Objective: Evaluation of the relationship between deep venous insufficiency and recurrent varicose veins (RVV). Design: Retrospective analysis of patients affected by RVV submitted to clinical examination, continuous-wave (CW) Doppler, duplex scanning and descending phlebography in cases of incompetence at groin level. Setting: Department of Vascular Surgery, Istituto Dermopatico dell'Immacolata (IRCCS), Rome. Patients: Two hundred and thirty-nine patients affected by RVV. Main outcome measures: CW Doppler ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…Furthermore, two thirds of the operated limbs with recurrence were found to develop venous reflux and varicose dilations in various new venous segments during the 5-year study period. These findings are in agreement with previous studies suggesting that primary CVD is a generalized disease with multifactorial etiology and developmental origin, [20][21][22] contributing significantly to recurrence after varicose vein surgery [22][23][24][25] as it could progressively involve any part of the lower limb's venous system.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, two thirds of the operated limbs with recurrence were found to develop venous reflux and varicose dilations in various new venous segments during the 5-year study period. These findings are in agreement with previous studies suggesting that primary CVD is a generalized disease with multifactorial etiology and developmental origin, [20][21][22] contributing significantly to recurrence after varicose vein surgery [22][23][24][25] as it could progressively involve any part of the lower limb's venous system.…”
Section: Discussionsupporting
confidence: 93%
“…22,23 We did not attempt to correct the DFV reflux in this series. This may result in the presence of the popliteal reflux extremities with anatomic connection between the DFV and popliteal vein.…”
Section: Discussionmentioning
confidence: 97%
“…In the control group, the authors found 11% recurrent varicosities, and we found a PDVI in 28% of 246 extremities affected by recurrent varicose veins. 1 Concerning the discordance about the observations that superficial venous surgery abolishes the deep venous reflux, we feel that this finding is correlated above all to the reflux grade. In our experience a third-to fourth-grade reflux cannot be abolished by saphenous surgery, but a first-to second-grade can, which is in accordance with the overload theory.…”
mentioning
confidence: 79%